Evaluasi Buku Ajar Bahasa Arab Kelas VII: Struktur, Materi, Dan Pendekatan Pembelajaran - Isnaini, Anisah (Ulumuna: Jurnal Studi Keilsman, 2025)
This research aims to analyze Arabic language textbooks. This research is intended to be used as material for the evaluation and development of more effective and contextual teaching materials. This research uses a descriptive qualitative approach, using the content/material analysis method. There are two sources of data for this research: primary and secondary. Data validity was tested using source triangulation. Based on the results of the researcher's analysis, the Arabic language learning guidebook for grade VII Madrasah Tsanawiyah is still suitable for use as a text reference book or reference book for Arabic language learning. The material or content in this book is in accordance with the objectives of language learning, adheres to the principles of foreign language learning, and pays attention to the cognitive aspects and skills of students. Although there are several shortcomings, this book still generally meets the standards of a good textbook